Pemasaran Produk Hasil Olahan Food Loss and Waste - Magetsari, Ovy Noviati Nuraini; Deliza Henny; Yosephina Endang Purba; Lavlimatria Esya (Dirkantara Indonesia, 2025)
The community service activity organized by the Faculty of Economics and Business, Trisakti University, on February 26, 2023, in Fokkalis, aimed to enhance the knowledge and skills of the community in managing Food Loss and Waste (FLW) into value-added products and marketing these processed products. The activities involved counseling, practical training, group discussions, and marketing assistance. The results showed an increase in participants' understanding of the concept of FLW and the importance of food waste management, as well as an improvement in skills to process food waste into marketable products such as compost, vegetable chips, and fruit jam. Activity evaluations indicated that hands-on training methods and marketing assistance were highly effective in enhancing participants' abilities. Furthermore, participants successfully developed several business plans based on FLW processing that have economic potential. The challenges faced included limited training time and inadequate facilities, which were addressed through adaptive and participatory approaches. To support the sustainability of the activity’s impact, ongoing training programs, increased collaboration with local stakeholders, and the use of digital technology to expand training and marketing access are needed. Thus, this activity successfully contributed positively to community empowerment and sustainable FLW management.